Pembuatan Sabun Cuci Piring Ecobubbles di Kelurahan Kramat Jati: Pengabdian - Vinda Cahya; Rachma Ikmaliya; Rahma Dania Larasaty; Rizky Yulia Nuraini; Sari Ayu; Shafaersa Saefullah; Siti Rahmaniyanti; Via Erista Nurjannah; Wardatul Ajwa; Wirdatul Laila Rohmah; Yansasni; Mayarni (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Household chemical pollution is a global concern, and one solution is producing eco-friendly dishwashing soap. This community engagement activity aimed to empower women of the PKK RW 02, Kramat Jati, East Jakarta, through training on making “Eco Bubbles” soap using simple ingredients: texapon, salt, and water. A participatory and demonstrative method was applied through initial observation, hands-on training, and evaluation via pre- and post-tests. Results showed 92% of participants understood the soap-making process, and 78% could perform it independently. The program also boosted participants’ confidence and encouraged household entrepreneurship. Success factors included high enthusiasm, strong teamwork, locally available materials, and community support, despite challenges like limited training time and low digital literacy. In conclusion, the activity effectively built new skills and created opportunities for sustainable micro-enterprises, with potential for replication in other areas to support eco-friendly households.